Semantic categories in the indigenous languages of Brazil - Hengeveld, Kees; Braga, Maria Luiza; Barbosa, Elisiene de Melo; Coriolano, Jaqueline Silveira; da Costa, Juliana Jezuino; Martins, Mariana de Souza; de Oliveira, Diego Leite; de Oliveira, Vinicius Maciel; Pereira, Luana Gomes; Santana, Liliane [UNESP]; do Carmo Santos, Cassiano Luiz; Soares, Viviane dos Ramos (John Benjamins Publishing Company, 2012)
This article investigates which semantic categories, as defined in Functional Discourse Grammar, formally manifest themselves in a sample of native languages of Brazil, and the extent to which the distribution of these manifestations across categories can be described systematically in terms of implicational hierarchies. The areas subjected to investigation are basic interrogative words, basic demonstrative words, and nominalization strategies.